A study on green building management practices in platinum office building / Soffia Adillah Selamat - Selamat, Soffia Adillah (2023)
Green building has become an important aspect in achieving a sustainable environment for the country and one of the highest achievements in green building certification is platinum certification that issued by Green Building Index Malaysia. However, the management of platinum green office buildings in Malaysia has been reported to have low numbers, with only 4% of the total green certified buildings achieving platinum status and from that only 4 buildings are office building. The number is significantly very low compared to the total number of green building certified. Why there is low numbers of platinum GBI certification? What are the elements should be considered in managing platinum green office buildings? Is that difficult to manage the GBI certification building? Therefore, this research aims to explore the management practices in platinum green office building and to investigate the challenges of management practices in platinum green office building. The study involves three (3) property managers of platinum-certified green office buildings in Kuala Lumpur and Putrajaya as participants. A qualitative approach was employed, specifically utilizing face-to-face semi-structured interviews and the content analysis are adopted.